Efficacy and Safety of Transarterial Radioembolization in Elderly Patients with Hepatocellular Carcinoma: A Single-Center Experience - Ümit Karaoğullarından; Yüksel Gümürdülü; Oğuz Üsküdar; Emre Odabaş; Hasan Selim Güler; Cansu Geçkalan; Burcu Arslan Benli; Anıl Delik; Asena Ayça Özdemir; Sedef Kuran (Turkish Journal of Gastroenterology 1, 2024)
Background/Aims: Hepatocellular carcinoma is a major cause of mortality and morbidity in both cirrhotic and non-cirrhotic patients, and most patients are suitable for locoregional and/or systemic therapy at the time of diagnosis. In this study, we aimed to determine the efficacy and safety of transarterial radioembolization in elderly patients. Materials and Methods: Patients diagnosed with hepatocellular carcinoma between 2013 and 2022 were screened retrospectively. The patients were divided into 2 groups: the elderly (age ≥70 years) and the young (age <70 years). Transarterial radioembolization response was evaluated according to the Response Evaluation Criteria in Solid Tumors. Results: Ninety patients were included in the young group, and 56 patients were in the elderly group. It was observed that male dominance was less in the elderly group (P > .05). Hepatitis B was the most common cause in both groups. There were no significant differences between groups with regard to morphological features of tumors [tumor focality (single; 62.2% and 60.7%, respectively) and maximal tumor diameter (6.9 and 6.55 cm, respectively)], transarterial radioembolization responses (51.1% and 39.3%, respectively), survival (9 and 8.5 months), and both early and late side effects (P > .05). Age was not found to be an effective factor in transarterial radioembolization response (P > .05). Conclusion: No differences in the safety and efficacy of transarterial radioembolization were observed between the groups. In addition, it was observed that age was not a predictive factor for adverse events. In elderly patients in the frail group, it should be considered that age alone should not be seen as a limitation in the transarterial radioembolization decision. Cite this article as: Karaoğullarından Ü, Gümürdülü Y, Üsküdar O, et al. Efficacy and safety of transarterial radioembolization in elderly patients with hepatocellular carcinoma: A single-center experience. Turk J Gastroenterol. 2024;35(3):204-211.